2011
DOI: 10.4049/jimmunol.1100450
|View full text |Cite
|
Sign up to set email alerts
|

Netting Neutrophils Induce Endothelial Damage, Infiltrate Tissues, and Expose Immunostimulatory Molecules in Systemic Lupus Erythematosus

Abstract: An abnormal neutrophil subset has been identified in the PBMC fractions from lupus patients. We have proposed that these “low density granulocytes” (LDGs) play an important role in lupus pathogenesis by damaging endothelial cells and synthesizing increased levels of proinflammatory cytokines and type I interferons. To directly establish LDGs as a distinct neutrophil subset, their gene array profiles were compared to those of autologous normal density neutrophils and control neutrophils. LDGs significantly over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

44
1,166
4
13

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 1,068 publications
(1,273 citation statements)
references
References 64 publications
44
1,166
4
13
Order By: Relevance
“…However, if dysregulated, it can also cause significant tissue injury. Inappropriate recruitment and activation of neutrophils are recognized as major contributors to organ damage in numerous inflammatory diseases, including inflammatory arthritis, acute respiratory distress syndrome, systemic lupus erythematosus, and acute glomerulonephritis (1)(2)(3)(4). Although our understanding of the molecular basis of neutrophil recruitment is well-developed, less is known about the interactions of neutrophils with other circulating immune cells during the development of the innate inflammatory response.…”
mentioning
confidence: 99%
“…However, if dysregulated, it can also cause significant tissue injury. Inappropriate recruitment and activation of neutrophils are recognized as major contributors to organ damage in numerous inflammatory diseases, including inflammatory arthritis, acute respiratory distress syndrome, systemic lupus erythematosus, and acute glomerulonephritis (1)(2)(3)(4). Although our understanding of the molecular basis of neutrophil recruitment is well-developed, less is known about the interactions of neutrophils with other circulating immune cells during the development of the innate inflammatory response.…”
mentioning
confidence: 99%
“…The newly discovered form of neutrophil cell death, NETosis, in which neutrophils throw out chromatin fibers (neutrophil extracellular traps; NETs) containing antibacterial peptidesand nuclear antigens, have been implicated in the SLE pathogenesis [121]. Increased NETosis [122] of SLE patients, as well as reduced capacity to degrade NETs have been demonstrated in vitro [123,124]. It has also been suggested that dysfunctional neutrophils can contribute to organ damage [121].…”
Section: Supar and Neutrophilsmentioning
confidence: 99%
“…De nombreuses études ont démontré l'existence d'une dérégulation des NET au cours du lupus, associant une augmentation de leur production et une altération de leur dégradation [15,16,37]. L'augmentation de production des NET est déclenchée par la présence de concentrations élevées de cytokines pro-inflammatoires (IL-18, IFN [interféron ]).…”
Section: Lupus éRythémateux Systémiqueunclassified